Protocol K - Erythrocyte measurements [Pratical guide of protocols: methods of verification of the ploidy] - Basurco B.; Carrillo M.; Felip A.; Zanuy S.; Herráez M.P. (Advances in fish reproduction and their application to broodstock management: a pratical manual for sea bass, 2009)
As triploid fish exhibit 50% more DNA per cell, total cell volume in triploids increase significantly in comparison to that of diploids to accommodate the extra amount of chromosomes. In particular, erythrocyte cellular and nuclear measurements are proportional to ploidy in teleost fish. On this basis, and assuming that erythrocytes in fish show an ellipsoidal shape, erythrocyte cellular and nuclear volume have been used as the criterion to identify polyploid fish in several studies. The objective of this Protocol is to report the accuracy of using erythrocyte cellular and nuclear measurements to identify triploid sea bass.